Cementochronology: A solution to assess mortality profiles from individual age-at-death estimates. (August 2018) - Lanteri, Laëtitia; Bizot, Bruno; Saliba-Serre, Bérengère; Gaudart, Jean; Signoli, Michel; Schmitt, Aurore
Abstract: Objectives: Because of methodological biases and statistical issues, individual age estimation has been considered too imprecise in reconstructing valid palaeodemographic mortality profiles. Recently, the standardized procedure of cementochronology (the tooth cementum annulations method) has reduced technical biases, thus increasing the accuracy of age estimates. This study aims to test the reliability of cementochronology in estimating the age distribution of an archaeological sample to then build the corresponding abridged life table to assess demographic parameters of the living population. Materials and methods: By combining cementochronology with probability density analysis, we assessed the cumulative probabilistic age-at-death distribution of 109 adults buried between the 16th and 18th centuries in Notre-Dame-du-Bourg Cathedral (France). We compared biological results to the age-at-death structure of the 1382 adults buried in the cathedral, calculated with historical sources from local death registers, and to a model life table specifically established for preindustrial populations. Results: Cementochronology is reliable for estimating the mortality profile of young and middle adult age categories but underestimates older age categories. Discussion: Taphonomy mainly explains the underestimation in elderly individuals. Although some issues remain to be addressedin order to properly implement the method and improve reliability, cementochronology makes a major contribution to palaeodemography, as it provides relatively reliable mortality profiles with a precision never attained before, thus offering new prospects for studying the mortality of past populations. Highlights: Cementochronology is reliable for estimating young and middle adult age categories. Cementochronology underestimates older age categories. Taphonomy mainly explains the underestimation in elderly individuals. Cementochronology provides a precision never attained before. Cementochronology offers new prospects for studying the mortality in the past.